1993
DOI: 10.2307/1940843
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Digestive Constraints on Basal Energy Metabolism in a Small Herbivorous Rodent

Abstract: McNab (1986, 1988) has hypothesized that mammals using food with low energy content should exhibit basal metabolic rates (BMR) lower than those expected on the basis of their body mass (mb). That is, those species that exploit food with low energy content and/or high cost of digestion tend to have low, mass—independent metabolic rates. To date there is not an experimental test of this pattern. The aim of this work was to examine experimentally the effect of diet quality on BMR, digestive efficiency, and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 39 publications
4
46
1
1
Order By: Relevance
“…P. aztecus proved to have lethargic behavior and low BMR and DMI, much lower than expected from the NPP of its natural environment (highly productive subtropical cloud forest). These observations of P. aztecus are in accord with previous arguments that animals consuming diets of low energy density tend to have low metabolic rates (3,38).…”
Section: Productivity or Variability?supporting
confidence: 92%
“…P. aztecus proved to have lethargic behavior and low BMR and DMI, much lower than expected from the NPP of its natural environment (highly productive subtropical cloud forest). These observations of P. aztecus are in accord with previous arguments that animals consuming diets of low energy density tend to have low metabolic rates (3,38).…”
Section: Productivity or Variability?supporting
confidence: 92%
“…Delayed reproductive response of degu to high herbage production in north-central Chile (Meserve et al, 1995) may also have ameliorating effects on ephemerals due to herbivory. Hence, whereas degus prefer high quality/low fiber plants when available (Veloso & Bozinovic, 1993;GutieH rrez & Bozinovic, 1998), they may generally be constrained to feeding on low quality/high fiber shrubs during the extensive dry years characteristic of this region.…”
Section: Discussionmentioning
confidence: 99%
“…RMR and NST play important roles in the regulation of energy balance (McNab 1986). Many small mammals regulate energy metabolism by changing RMR and NST in adapting to environmental changes (Veloso & Bozinovic 1993). RMR and NST decreased significantly during food deprivation in E. miletus.…”
Section: Food Intake Rmr and Nstmentioning
confidence: 99%
“…And it has been shown that changing food quality and quantity will lead to a marked variation of energy expenditure (Veloso & Bozinovic 1993). Many studies have demonstrated that low food quality induces a decrease in RMR in mammals (McNab 1986;Veloso & Bozinovic 1993).…”
Section: Introductionmentioning
confidence: 99%